ANALISIS RASIO VOLUME KENDARAAN TERHADAP KAPASITAS RUAS JALAN TANJUNGSARI-JATINANGOR KABUPATEN SUMEDANG - Nasuha, Ari; Saepudin, Uu; Defiana, Yanti (Jurnal Ilmiah Teknik Sipil, 2026)
The Tanjungsari–Jatinangor Road in Sumedang Regency is a major corridor with high mobility that frequently experiences traffic congestion. The increasing number of vehicles and high side friction factors such as on-street parking, vehicle movements in and out of adjacent areas, and commercial activities have contributed to a decline in road performance. This condition is reflected in the increasing volume-to-capacity ratio and degree of saturation. This study aims to analyze the volume- to-capacity ratio (V/C) and determine the road level of service (LoS) on the Tanjungsari–Jatinangor segment. The research employed a field survey during peak hours and analysis based on the Indonesian Highway Capacity Manual (PKJI) 2023. The collected data include traffic volume, side friction, free-flow speed, and road capacity. The results indicate that the peak traffic volume reached 2,129 pcu/hour with a road capacity of 2,585 pcu/hour. The calculated V/C ratio of 0.82 and degree of saturation (DS) of 0.82 show that traffic conditions are nearing capacity. According to PKJI 2023, the Level of Service (LoS) is classified as D, indicating unstable flow, frequent delays, and reduced comfort for road users. After applying a side friction reduction scenario, the capacity increased to 2,818 pcu/hour, the DS decreased to 0.75, and the LoS improved to C. Therefore, side friction control, on-street parking management, and improved traffic management are necessary to enhance road performance.